2009
DOI: 10.1152/physiolgenomics.90398.2008
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of protein biosynthesis genes in liver and muscle of hibernating black bears (Ursus americanus)

Abstract: We conducted a large-scale gene expression screen using the 3,200 cDNA probe microarray developed specifically for Ursus americanus to detect expression differences in liver and skeletal muscle that occur during winter hibernation compared with animals sampled during summer. The expression of 12 genes, including RNA binding protein motif 3 (Rbm3), that are mostly involved in protein biosynthesis, was induced during hibernation in both liver and muscle. The Gene Ontology and Gene Set Enrichment analysis consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
125
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(144 citation statements)
references
References 39 publications
15
125
1
Order By: Relevance
“…In the liver, mbd3 and mecp2 mRNA levels differed between animals that were euthermic in the cold room and those in early arousal. We speculate that mbd3 transcription may support the activation of rRNA, as seen in previous studies (Brown and Szyf, 2007), consistent with the need for rapid reactivation of liver ribosomal protein synthesis when animals arouse from bouts of torpor (Epperson et al, 2004;Fedorov et al, 2009). Additionally, in muscle, MeCp2 has been reported to be involved in myogenesis as its role in forming pericentric heterochromatic centers is important for differentiation (Brero et al, 2005).…”
Section: Uncoupled Transcription Of Epigenetic Regulators From Genomisupporting
confidence: 81%
“…In the liver, mbd3 and mecp2 mRNA levels differed between animals that were euthermic in the cold room and those in early arousal. We speculate that mbd3 transcription may support the activation of rRNA, as seen in previous studies (Brown and Szyf, 2007), consistent with the need for rapid reactivation of liver ribosomal protein synthesis when animals arouse from bouts of torpor (Epperson et al, 2004;Fedorov et al, 2009). Additionally, in muscle, MeCp2 has been reported to be involved in myogenesis as its role in forming pericentric heterochromatic centers is important for differentiation (Brero et al, 2005).…”
Section: Uncoupled Transcription Of Epigenetic Regulators From Genomisupporting
confidence: 81%
“…Thus, protection of skeletal muscles from the usual deleterious effects of disuse is not intrinsic to bears year-round and arises from changes in bear physiology occurring during hibernation. Consistent with this finding, gene expression for protein catabolism is downregulated and for protein synthesis is upregulated in skeletal muscle, liver and heart tissues of hibernating black bears relative to summer-active bears (Fedorov et al, 2009;Fedorov et al, 2011).…”
Section: Discussion Differences In the Effects Of Denervation Betweensupporting
confidence: 63%
“…Rates of both protein degradation and synthesis can be reduced by up to 70% in the skeletal muscle of hibernating bears (Lohuis et al, 2007). However, more recent studies found increased expression of mRNAs largely involved in protein biosynthesis and ribosome biogenesis in the muscles of both hibernating bears and arctic ground squirrels relative to those of summer active animals, suggesting that induction of translation could be enhanced at different stages of hibernation (Fedorov et al, 2014(Fedorov et al, , 2009. Despite the need for global suppression of energetically expensive processes such as transcription and translation during dormancy (Storey and Storey, 2010), a number of recent studies have emphasised the importance of maintaining protein synthesis in hibernating muscle through activation of the mTOR signalling cascade (Andres-Mateos et al, 2013;Fedorov et al, 2014;Lee et al, 2010;Nowell et al, 2011).…”
Section: Regulation Of Protein Synthesismentioning
confidence: 99%